The Aging and Retirement: A Comparative Study on the Pension Policy in South Korea and Indonesia - Getar Hati; Ari Lazuardi Pratama (Asian Social Work Journal, 2022)
The aging group in society faces challenging situations in most countries. This paper discusses comparing the aging challenge and pension policy to overcome the problems. As one of the most aging population countries globally, South Korea has become a good representative to learn about the aging context. Meanwhile, Indonesia as a populous country with a gradually growing aging population from year to year. The article analyses that even though South Korea and Indonesia have a similar threat for aging population growth, these two countries face different situations. South Korea faces a low fertility threat, and Indonesia faces poverty in the aging population. Therefore, pension policy as social security and protection are discussed through the state and corporate pillars in implementing the pension scheme. However, the pension policy implementation in South Korea should be supported by strengthening social networks to enhance the elderly group. Meanwhile, in Indonesia, there is a need to increase people's awareness in participating in the pension plan to enhance life quality in the old ages.